2022
DOI: 10.3390/jcm11020352
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Prior to COVID-19 Infection Has No Impact on 6 Months Mortality: A Propensity Score–Matched Cohort Study

Abstract: The coronavirus disease 2019 (COVID-19) shows high incidence of thromboembolic events in humans. In the present study, we aimed to evaluate if anticoagulation prior to COVID-19 infection may impact clinical profile, as well as mortality rate among patients hospitalized with COVID-19. The study was based on retrospective analysis of medical records of patients with laboratory confirmed SARS-CoV-2 infection. After propensity score matching (PSM), a group of 236 patients receiving any anticoagulant treatment prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…Initial higher level of INR in males high-risk C 2 HEST score stratum seems to support this thesis. Although the principal clinical manifestation of severe COVID-19 is a respiratory failure with a coexisting uncontrolled immune reaction, subjects with COVID-19 show a high incidence of thromboembolic events [ 29 ], particularly in fatal cases [ 30 ], however antithrombotic treatment prior to COVID-19 infection is unlikely to have a protective effect [ 31 ]. Bleeding complications in subjects with COVID-19 give rise to justifiable concerns [ 32 , 33 ] and should always be considered before applying anticoagulation in patients with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Initial higher level of INR in males high-risk C 2 HEST score stratum seems to support this thesis. Although the principal clinical manifestation of severe COVID-19 is a respiratory failure with a coexisting uncontrolled immune reaction, subjects with COVID-19 show a high incidence of thromboembolic events [ 29 ], particularly in fatal cases [ 30 ], however antithrombotic treatment prior to COVID-19 infection is unlikely to have a protective effect [ 31 ]. Bleeding complications in subjects with COVID-19 give rise to justifiable concerns [ 32 , 33 ] and should always be considered before applying anticoagulation in patients with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The authors report that crude hospital mortality rate was higher for medicated patients, but not so after multivariable adjustments. Similarly, an observational study from Poland demonstrated that pre-COVID-19-anticoagulation had no impact on middle-term mortality [25]. A nationwide pharmacoepidemiologic study from Sweden [13] assessed impact of antithrombotic medication on hospitalization and a composite outcome of ICU admission and death from February to May 2020.…”
Section: Discussionmentioning
confidence: 99%
“…13 Yet, observational studies have produced conflicting data on whether baseline use of oral anticoagulants including VKAs improves or worsens clinical outcomes among patients hospitalized with COVID-19 pneumonia. [65][66][67] Existing guidance does not compare oral anticoagulant therapies for COVID-19 inpatients and there is a lack of high-quality studies specifically on continuation of pre-hospital VKAs during admission. 59,68 A major question in the anticoagulation of patients hospitalized for COVID-19 pneumonia is whether to continue DOACs in those patients with pre-existing indications.…”
Section: Statement 10mentioning
confidence: 99%
“…Patients prescribed VKA therapy who develop COVID‐19 pneumonia exhibit a decreased time in therapeutic range and increased variance of INR measurements 13 . Yet, observational studies have produced conflicting data on whether baseline use of oral anticoagulants including VKAs improves or worsens clinical outcomes among patients hospitalized with COVID‐19 pneumonia 65–67 . Existing guidance does not compare oral anticoagulant therapies for COVID‐19 inpatients and there is a lack of high‐quality studies specifically on continuation of pre‐hospital VKAs during admission 59,68 …”
Section: Hospitalization Periodmentioning
confidence: 99%